Visualizing segmental contributions to whole-body angular momentum in the rotational shot put and discus throw - Kipp, K.; Ahn, N (ISBS Proceedings Archive: Vol. 42: Iss. 1, 2024)
The purpose of this study was to develop a method to visualize the contributions of the free limbs to whole-body angular momentum (L) during the rotational shot put and discus throw. Digital video of track and field throwers were recorded as they performed several shot put and discus throw attempts. Videos were processed with markerless motion capture technology, which was used to generate segment center-of-mass (COM) positions. Whole-body L in the global coordinate system was calculated as the sum of transfer terms of the legs, arms, and trunk segments. To visualize transverse plane L generated by the legs and arms, the area "swept out" by each segment was plotted and then "filled" based on the magnitude of L. Qualitative analysis of the visualizations show they provide an intuitive understanding of how the limbs generate L and contribute to overall throwing performance.